Scope of duty, counterfactual analysis and birth defects: The challenging case of Khan v Meadows - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2021)
The tort of negligence has evolved into a sophisticated and calibrated framework. Even then, aspects of this elaborate structure are constantly being tweaked and, sometimes, challenged. Most recently, in the UKSC decision of Khan v Meadows, the spotlight is thrown on scope of duty analysis against the challenging backdrop of medical negligence and unwanted birth defects. The judgment of the majority suggests there is more that needs to be considered at the stage of damages, and that the sequential framework of negligence may benefit from some rearrangement.